Auditory-Based Cognitive Training Drives Short- and Long-Term Plasticity in Cortical Networks in Schizophrenia. Issue 1 (21st November 2020) - Koshiyama, Daisuke; Miyakoshi, Makoto; Thomas, Michael L; Joshi, Yash B; Molina, Juan L; Tanaka-Koshiyama, Kumiko; Nungaray, John A; Sprock, Joyce; Braff, David L; Swerdlow, Neal R; Light, Gregory A
Abstract: Schizophrenia patients have widespread deficits in neurocognitive functioning linked to underlying abnormalities in gamma oscillations that are readily measured by the 40 Hz auditory steady-state response (ASSR). Emerging interventions such as auditory-based targeted cognitive training (TCT) improve neurocognitive function in patients. While acute ASSR changes after 1 hour of TCT predict clinical and cognitive gains after a 30-hour course of TCT, the neural substrates of underlying short- and long-term TCT interventions are unknown. To determine the neural substrates underlying TCT-associated ASSR changes, a novel data analysis method was applied to assess the effective connectivity of gamma-band ASSR among estimated cortical sources. In this study, schizophrenia patients ( N = 52) were randomized to receive either a treatment as usual (TAU; N = 22) or TAU augmented with TCT ( N = 30). EEG recordings were obtained immediately before (T0) and after 1 hour of either computer games (TAU) or cognitive training (TCT; T1), and at 65 ± 15 days (mean ± SD) post-randomization (T2). Results showed increased connectivity from the left ventral middle cingulate gyrus to the left posterior cingulate gyrus, accompanied by decreased connectivity from the left Rolandic operculum (a region that includes auditory cortex) to the right ventral middle cingulate gyrus after 1 hour of TCT. After 30 hours, decreased connectivity from the frontal cortex to a region near the calcarine sulcus were detected. Auditory-based cognitive training drives short- and long-term plasticity in cortical network functioning in schizophrenia patients. These findings may help us understand the mechanisms underlying cognitive training effects in schizophrenia patients and enhance the development of pro-cognitive therapeutics.